AKULTURASI NILAI SOSIAL BUDAYA DALAM TRADISI TONJOKAN (HANTARAN) - Jayani, Nanang; Purnama, Mita; Lidiawati, Citra; Habibi, Sanial; Rotari, Septi (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
Indonesia's cultural diversity requires serious preservation efforts in accordance with the constitutional mandate, one of which is reflected in the Tonjokan Tradition in Pangestu Village, Banyuasin Regency. This research focuses on analyzing the actualization of the acculturation of socio-cultural values in this tradition of dowry offerings to understand its existence amidst changing times. Using qualitative methods with a descriptive approach, data collection was conducted through observation, documentation, and in-depth interviews with traditional leaders and community members selected through purposive sampling. The research findings reveal that Tonjokan, brought by Javanese transmigrants since 1971, is a social mechanism in the form of food gifts as invitations to celebrations that applies to all levels of society regardless of social status. This tradition contains substantial values such as solidarity, mutual cooperation, respect, and strengthening ties. Furthermore, its implementation is proven to be in line with Article 18B paragraph (2) of the 1945 Constitution and Regional Regulation No. 2 of 2022 concerning the preservation of customs and traditions. It is concluded that the actualization of values in Tonjokan serves a vital function as a bond of social cohesion and a reference for adaptive multiculturalism, making its sustainability a crucial instrument in maintaining harmony and the cultural identity of the local community. ABSTRAK Keberagaman budaya di Indonesia memerlukan upaya pelestarian yang serius sesuai amanat konstitusi, salah satunya tercermin dalam Tradisi Tonjokan di Desa Pangestu, Kabupaten Banyuasin. Penelitian ini berfokus pada analisis aktualisasi akulturasi nilai sosial budaya dalam tradisi hantaran tersebut guna memahami eksistensinya di tengah perkembangan zaman. Menggunakan metode kualitatif dengan pendekatan deskriptif, pengumpulan data dilakukan melalui observasi, dokumentasi, dan wawancara mendalam dengan tokoh adat serta masyarakat yang dipilih melalui purposive sampling. Temuan penelitian mengungkapkan bahwa Tonjokan, yang dibawa oleh transmigran Jawa sejak 1971, merupakan mekanisme sosial berupa hantaran makanan sebagai undangan hajatan yang berlaku bagi seluruh lapisan masyarakat tanpa memandang status sosial. Tradisi ini mengandung nilai-nilai substansial seperti solidaritas, gotong royong, penghormatan, dan penguatan tali silaturahmi. Selain itu, pelaksanaannya terbukti selaras dengan UUD 1945 Pasal 18 B ayat (2) dan Perda No 2 Tahun 2022 tentang pelestarian adat istiadat. Disimpulkan bahwa aktualisasi nilai dalam Tonjokan berfungsi vital sebagai pengikat kohesi sosial dan referensi multikulturalisme yang adaptif, sehingga keberlanjutannya menjadi instrumen penting dalam menjaga harmonisasi dan identitas kultural masyarakat setempat.